Digitalization of banking services and financial inclusion in Botswana - Mpowe, Emmanuel (University of the Witwatersrand, Johannesburg, 2023)
The purpose of the study was to evaluate the level of digitalization of banking or financial services in Botswana. The study also sought to understand the association between digitalization and financial inclusion Furthermore, the research also studied the association of macro level determinants of financial inclusion such as GDP per capita and employment to adult population with financial inclusion. The study used secondary data collected mainly from the reserve bank of Botswana’s reports published on their website, Central Statistics Office and annual report of a selected commercial banks. Annual spending on ICT by commercial banks was used as a proxy for digitalization. The study used time series data from 2006 to 2020. Regression and correlation techniques were performed on the selected variables with financial inclusion as a dependent variable. The result from the analysis suggested that there is a significant positive association between ICT spend or digitalization of banking services and financial inclusion. This findings were in support of the hypothesis formulated from the existing literature which also suggested that digital financial services are more likely to increase the level of financial inclusion. The study also evaluated the impact of GDP and employment rate on financial inclusion. The findings suggested that both variables have a positive correlation with financial inclusion.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Financial inclusion; Digitalization; Gross Domestic Product; GDP per capita; Employment; Adult population; Penetration; Availability; Usage; Commercial Banks; UCTD; SDG-8: Decent work and economic growth